Is there a relation between loss of shoulder external rotation and sternoclavicular joint disorders? - Pisanu, Francesco; Verderosa, Vincenzo; Perego, Stefano; Cutaia, Rosario; Ciatti, Corrado; Manunta, Andrea Fabio; Doria, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Scapulothoracic movements are essential in shoulder kinematics and can partially compensate stiffness and loss of motion of glenohumeral joint. The scapulothoracic movement is strictly dependent on the translation and rotation of the clavicle at the sternoclavicular joint (SCJ), this being the only true joint between the axial and the upper appendicular skeleton. Aim of the study is to define a possible correlation between loss of shoulder external rotation following surgery for anterior shoulder instability and long-term sternoclavicular joint disorders. Methods: A group of 20 patients and a group of 20 healthy volunteers were studied. Results: In the statistical analysis of the patient group and of the two groups jointly, the association between the reduction of shoulder external rotation and the onset of disorder of SCJ appeared statistically significant. Conclusions: Our results provide support for an association between some disorders of the SCJ and the alterations of the shoulder kinematics associated with a reduction of ROM in external rotation. Our sample is too small to allow definitive conclusions to be drawn. These results, if confirmed by larger studies, could help us further clarify the complex kinematics of the shoulder girdle.